A Co(II)-based metallo-supramolecular polymer as a novel enzyme immobilization matrix for electrochemical glucose biosensing. (October 2016) - Hsu, Chih-Yu; Sato, Takashi; Moriyama, Satoshi; Higuchi, Masayoshi
Graphical abstract: Highlights: Novel glucose oxidase immobilization matrix for glucose biosensor is described. Efficient and precise glucose electrochemical detection is achieved. The biosensor has good selectivity/stability, with ease of electrode preparation. Abstract: A Co(II)-based metallo-supramolecular polymer (polyCo) was used as a novel matrix to immobilize glucose oxidase (GOx) for enzymatic glucose sensing. A facile fabrication of a modified glassy carbon electrode (GCE) was achievable by a one-step co-immobilization method. UV–vis spectroscopy and cyclic voltammetry were used to characterize the electrochemical biosensor and the sensing mechanism of the reaction on the polyCo-modified GCE. After the optimization of composition and loading of the polyCo/GOx GCE, the fabricated sensor demonstrated excellent amperometric quantification of glucose, with high sensitivity (47.1 μA mM −1  cm −2 ) in the linear range of up to 1.4 mM. The selectivity, based on the enzyme matrix without any pretreatment, was also sufficiently high. The outstanding stability of the sensor supported our assumption that metallo-supramolecular polymers can be used as electrode materials for glucose biosensors.